The Practicality of Macromedia Flash-Based Learning Media to Improve Students Critical Thinking Skills Senior High School Students - Hairullah Aminudin; Mochamad Arief Soendjoto; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
Interactive learning resources contribute to the success of the learning process and students' critical thinking skills but have not been developed equally in every subject. This study aims to obtain the practicality of Macromedia Flash in improving the critical thinking skills of Kurau 1 State Senior High School students. This type of research is a Tessmer formative test with research subjects of 30 students of Kurau 1 State Senior High School. The research data were analyzed descriptively, practicality data included the use of instructional media and student responses, showing that Macromedia Flash was developed practical for used in learning and could improve the critical thinking skills of senior high school students.AbstrakSumber belajar interaktif memberikan kontribusi terhadap kesuksesan proses pembelajaran dan kemampuan berpikir kritis siswa, akan tetapi belum dikembangkan secara merata pada setiap mata pelajaran. Penelitian ini bertujuan untuk mendapatkan kepraktisan Macromedia Flash dalam meningkatkan keterampilan berpikir kritis siswa SMAN 1 Kurau. Jenis penelitian yang digunakan adalah uji formatif Tessmer dengan subjek penelitian 30 siswa SMAN 1 Kurau. Data penelitian dianalisa secara diskriptif, data kepraktisan meliputi keterlaksanaan penggunaan media pembelajaran dan respon siswa, menunjukkan bahwa Macromedia Flash yang dikembangkan praktis untuk digunakan dalam pembelajaran serta dapat meningkatkan kemampuan berpikir kritis siswa SMA.